TEKNOLOGI ZONE AGROEKOLOGI DALAM PEMBANGUNAN PERTANIAN BERWAWASAN LINGKUNGAN - Adnyana, I Made (Bumi Lestari; Vol 6 No 1)
Technology of agroecologycal zonning is a land evaluation to using specific area especially in agriculture with friendly environment. Agroecologycal zonning based on fisically environment elements i.e., climate, physiography and landform, soil resources, vegetation and land use. Alternative commodities that will be devolloped based on social economy factors. In area with stable land using (East and centre of Buleleng) the commodities that will be choised : adaptive, profitable, and acceptability. In area with not yet stable land using (west of Buleleng) will be purposed with agroecologycal zonning as (1) at slopping area for suitable and profitable annual cropping, (2) at hilly area for multiple cropping, (3) in mountainous area with slope < 40% for multiple cropping and estate, whereas, if slope >40% and elevation >700 m over the sea level for plants conservation.
Keywords: agroecology, slopy, hilly, mountainous, conservation